The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12913-017-2386-x
|View full text |Cite
|
Sign up to set email alerts
|

Greater involvement of HIV-infected peer-mothers in provision of reproductive health services as “family planning champions” increases referrals and uptake of family planning among HIV-infected mothers

Abstract: BackgroundIn 2012, Makerere University Johns - Hopkins University, and Mulago National Referral Hospital, with support from the National Institute of Health (under Grant number: NOT AI-01-023) undertook operational research at Mulago National Hospital PMTCT/PNC clinics. The study employed Peer Family Planning Champions to offer health education, counselling, and triage aimed at increasing the identification, referral and family planning (FP) uptake among HIV positive mothers attending the clinic.MethodsThe Pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Interventions that focus on efficient and acceptable delivery of comprehensive family planning counselling are needed, especially in high HIV-burden rural settings where health systems are relatively weaker and missed opportunities for PMTCT may be more likely. Delivery of these services could be expanded and sustained through trained community workers or lay peer mentors to overcome the relative lack of professional healthcare workers and inadequate counselling skills that often limit provision of family planning counselling to HIV-infected women [42, 44]. Of note, structured peer support provided by Mentor Mothers emerged as a negative correlate of reported condom use when compared with no contraception.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that focus on efficient and acceptable delivery of comprehensive family planning counselling are needed, especially in high HIV-burden rural settings where health systems are relatively weaker and missed opportunities for PMTCT may be more likely. Delivery of these services could be expanded and sustained through trained community workers or lay peer mentors to overcome the relative lack of professional healthcare workers and inadequate counselling skills that often limit provision of family planning counselling to HIV-infected women [42, 44]. Of note, structured peer support provided by Mentor Mothers emerged as a negative correlate of reported condom use when compared with no contraception.…”
Section: Discussionmentioning
confidence: 99%
“…The PURE Malawi trial found that, compared to the prevailing standard of care, facility‐ and community‐based peer support models led to better uptake of ART (81% vs. 86% and 90% respectively) and retention at 24 months (66% vs. 80% and 83% respectively) [71]. Other studies have shown that peer‐centred approaches can effectively be combined with other interventions [72] and encourage other reproductive health behaviours [73]. These trial findings are largely supported by qualitative research, which confirm the overall feasibility and acceptability of the intervention [74‐76], including among adolescents [77].…”
Section: Resultsmentioning
confidence: 99%
“… 37 38 Given observed gaps in adolescent access to sexual and reproductive healthcare and family planning, unplanned pregnancies, and experiences of stigma and mental health challenges, programmes can further train and leverage YPM to lead work with adolescents in these areas. 39–41 …”
Section: Discussionmentioning
confidence: 99%
“… 63 Urgent measures are needed to address the needs of adolescents, particularly for food access or assistance, financial interventions, and improved access to family planning and PMTCT care, including through YPM interventions. 39 41 67 Further research is needed to understand the full extent of impacts of the COVID-19 pandemic on the adolescent HIV care cascade and on perinatal HIV transmission. 22 68 …”
Section: Discussionmentioning
confidence: 99%